Fatal Renal Abscess Caused by Porphyromonas gingivalis and Subcapsular Hemorrhage, Japan - Yuichiro Atagi; Yoshito Homma; Sadamu Yamashi; Ken Kikuchi; Yoji Nagashima (Emerging Infectious Diseases)
A 61-year-old man in Japan with abdominal pain was suspected of having a renal tumor. Despite initial treatment, his condition rapidly deteriorated, leading to death. Postmortem examination revealed a renal abscess and sepsis caused by Porphyromonas gingivalis. This case underscores the need to consider atypical pathogens in renal masses.